2014
DOI: 10.1016/j.fob.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term exposure of nontumorigenic human bronchial epithelial cells to carcinogenic chromium(VI) compromises their respiratory capacity and alters their bioenergetic signature

Abstract: HighlightsChromium(VI) impaired respiration and increased glycolytic flux in BEAS-2B cells.Cr(VI)-exposed cells shifted to a more fermentative metabolism.This metabolic shift was in line with a decreased β-F1-ATPase/GAPDH protein ratio.Increased oxidative stress levels suggest impairment of antioxidant defenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 49 publications
(68 reference statements)
1
6
1
Order By: Relevance
“…Previous studies from our group suggested increased proliferation rates for BEAS-2B cells exposed to mild Cr(VI) concentrations (0.1-2 lM) (Costa et al 2010;Ferreira et al 2012;Cerveira et al 2014). By determining the doubling times of Cr(VI)-exposed cultures, we now confirmed that Cr(VI) produces a concentration-dependent increase in proliferation rate (Fig.…”
Section: Cr(vi) Stimulates Cellular Proliferationsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous studies from our group suggested increased proliferation rates for BEAS-2B cells exposed to mild Cr(VI) concentrations (0.1-2 lM) (Costa et al 2010;Ferreira et al 2012;Cerveira et al 2014). By determining the doubling times of Cr(VI)-exposed cultures, we now confirmed that Cr(VI) produces a concentration-dependent increase in proliferation rate (Fig.…”
Section: Cr(vi) Stimulates Cellular Proliferationsupporting
confidence: 79%
“…It is well established, though, that Cr(VI) is an inducer of oxidative, genotoxic and proteotoxic stress, through the generation of the above-mentioned reactive species, some of them potent oxidizers (Fornace et al 1981;Tsapakos and Wetterhahn 1983;Myers 2012;Urbano et al 2012;Li et al 2015). Cr(VI)induced deregulated cellular energetics, as shown by us (Rodrigues et al 2009;Goncalves et al 2011;Ferreira et al 2012;Cerveira et al 2014) and others (Liu et al 2010;Myers et al 2010;Molina-Jijon et al 2011;Xiao et al 2012a;Abreu et al 2014), likely constitutes an additional major stressor.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The resultant intermediates further react with H 2 O 2 to generate a spectrum of reactive oxygen species (ROS) containing hydroxyl radicals, singlet oxygen, superoxide, and hydrogen peroxide via the Fenton pathway. 12 15 Consequently, excessive ROS interaction with these intermediates may give rise to oxidative stress and DNA damage, including chromium–DNA adducts, DNA strand breaks, and DNA–protein cross-links (DPCs), all of which are unstable factors of mutagenic effects. 16 , 17 Therefore, the International Agency for Research on Cancer (IARC) has classified Cr(VI) as a group I carcinogen.…”
Section: Introductionmentioning
confidence: 99%
“…Beas-2B cells were plated in 6 well plates at an initial density of 300 cells per well [99]. The medium was refreshed with incinerated thermoplastic-containing AEGM, and 0.5 μM B[a]P or DMSO vehicle as control treatments.…”
Section: Clonogenic Assaymentioning
confidence: 99%